Jeff Kennett address at the National Press Club on 6 October 1993 - Kennett, Jeff.; Victoria. Premier (1992-1999 : Kennett); National Press Club (Australia) (1993)
Kennett, Premier of Victoria, attacks what he perceives as a lack of leadership and direction in Australia, particularly at the Federal level.
Copies available on cassette.
Photographs available.
Also available online
Transcript unavailable.
Keywords: Kennett, Jeff; Politicians -- Victoria; Australia -- Politics and government -- 1990-2001.; Australia -- Economic conditions -- 1990-2001.; Premiers